ANALISIS FAKTOR-FAKTOR KEBIJAKAN HUTANG PADA PERUSAHAAN PROPERTI DAN REAL ESTATE - Vina Heresta; Susanto Salim (Jurnal Paradigma Akuntansi, 2023)
This study aims to analyze the effect of earning volatility, liquidity, asset structure, free cash flow, and sales growth on debt policy in property and real estate companies for the 2017-2019 period. This type of research is descriptive research using a purposive sampling method in determining the sample. The sample in this study used 35 property and companies real estate listed on the Indonesia Stock Exchange. Hypothesis testing in this study using multiple regression analysis methods. This study performs data processing using software SPSS(Statistical Package for the Social Sciences) version 25. The results show that earning volatility and sales growth have no significant effect on debt policy, liquidity has a significant negative effect on debt policy. asset structure has a significant positive effect on debt policy, and free cash flow has a significant negative effect on debt policy.